Mengembangkan Motorik Halus Anak Menggunakan Model Project Based Learning, Metode Demonstrasi Dan Media Kertas Kokoru Di Kelompok B TK Betlehem - Nor Hafidzah; Ratna Purwanti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The background of this study is the low fine motor skills of children in imitation activities, which are caused by the less than optimal use of learning media that can stimulate children's finger skills and the minimal involvement of physical activity in the learning process which tends to be one-way. This study aims to describe the activities carried out by teachers and children, as well as the development of children's fine motor skills, especially in terms of imitation of shapes, through a qualitative approach with the PTK method for 4 meetings. The research findings show that the combination of the Project Based Learning model, demonstration methods, and the use of kokoru paper media has been proven to be able to increase children's activities and support fine motor development. Thus, it is hoped that these findings can help principals, teachers, and future researchers to improve the quality of early childhood education.